Operational Efficiency and Financial Performance of Agro Processing Firms in Acholi Sub-Region - Gladys Angee; John Baguma Muhunga Kule; John Rwakihembo; Pereez Nimusima; Mshilla Maghanga; Moreen Niwaha (International Journal of Entrepreneurship, 2026)
Purpose: Agro-processing enterprises constitute a vital component of Uganda’s industrial development agenda due to their contribution to value addition, employment generation, income creation, and economic growth. However, many firms continue to experience weak financial performance characterized by low profitability, liquidity constraints, and limited competitiveness. Since financial success is essential for firm survival, growth, and long-term viability, understanding the internal capabilities that drive superior performance remains imperative. This study examined the effect of operational efficiency on the financial performance of agro-processing firms in the Acholi Sub-region of Uganda. Methodology: The study employed a cross-sectional survey design within an explanatory mixed-methods framework. Data were collected from 242 respondents drawn from 70 agro-processing firms in the Acholi Sub-region of Uganda using structured questionnaires, complemented by 13 key informant interviews. Data analysis involved descriptive statistics, Pearson correlation analysis, and simple linear regression. Qualitative data were analyzed using thematic analysis to complement the quantitative findings. Findings: The study found a strong positive and statistically significant relationship between operational efficiency and financial performance among agro-processing firms (r = 0.840, p < 0.001). Regression results revealed that operational efficiency significantly predicts financial performance (β = 0.840, B = 0.738, p < 0.001), accounting for 70.5% of the variation in financial performance (R² = 0.705). Unique Contribution to theory, Practice and Policy: Given the significant contribution of operational efficiency to financial performance, agro-processing firms should prioritize capacity utilization and cycle time management as core strategic capabilities for achieving sustainable competitiveness. Firms should adopt lean operational practices, invest in modern processing technologies, and strengthen resource optimization systems to reduce production costs and improve financial outcomes. At the policy level, interventions aimed at improving infrastructure, technological upgrading, and managerial capabilities are necessary to address external constraints that may limit the financial gain.
Keywords: Operational Efficiency; Financial Performance; Agro-Processing Sector; Capacity Utilization; Cycle Time